ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK: (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kota Batu) - Angga Lie Fauzi; Abdul Hakim; Choirul Saleh (Jurnal Administrasi Publik, 2023)
This study measured and analyzed public satisfaction with the public services in Dinas Kependudukan dan Pencatatan Sipil Kota Batu. This research is a quantitative study with survey data collection procedures. 384 samples were sampled through quota sampling. The research data were analyzed using product moment analysis to determine the multiple regression of independent variables (tangibles, reliability, responsiveness, assurance and empathy) to dependent variables (community satisfaction). Survey results show that the quality of service and community satisfaction are in good category. Statistical test resulted in the regression equation Y=1.39+0.365X1+0.339X2+0.355X3+0.457X4+0.439X5. Hypothesis test showed that the variables studied had a partial and simultaneous significant influence on community satisfaction. The determination test showed an R2 value of 0.895, which means that 89.5% of public satisfaction was influenced by this variable while the remaining 10.5% was influenced by other variables. The Effective Donation calculation shows that the empathy variable has the largest donation value of 24.2%.